Sirt5 regulates chondrocyte metabolism and osteoarthritis development through protein lysine malonylation - Liu, Huanhuan; Binoy, Anupama; Ren, Siqi; Martino, Thomas C; Miller, Anna E; Willis, Craig R G; Veerabhadraiah, Shivakumar R; Sukul, Abhijit; Bons, Joanna; Rose, Jacob P; Schilling, Birgit; Jurynec, Michael J; et al. (bioRxiv, 2024)
Chondrocyte metabolic dysfunction plays an important role in osteoarthritis (OA) development during aging and obesity. Protein post-translational modifications (PTMs) have recently emerged as an important regulator of cellular metabolism. We aim to study one type of PTM, lysine malonylation (MaK) and its regulator Sirt5 in OA development. Human and mouse cartilage tissues were used to measure SIRT5 and MaK levels. Both systemic and cartilage-specific conditional knockout mouse models were subject to high-fat diet (HFD) treatment to induce obesity and OA. Proteomics analysis was performed in and WT chondrocytes. SIRT5 mutation was identified in the Utah Population Database (UPDB). We found that SIRT5 decreases while MAK increases in the cartilage during aging. A combination of Sirt5 deficiency and obesity exacerbates joint degeneration in a sex dependent manner in mice. We further delineate the malonylome in chondrocytes, pinpointing MaK's predominant impact on various metabolic pathways such as carbon metabolism and glycolysis. Lastly, we identified a rare coding mutation in that dominantly segregates in a family with OA. The mutation results in substitution of an evolutionally invariant phenylalanine (Phe-F) to leucine (Leu-L) (F101L) in the catalytic domain. The mutant protein results in higher MaK level and decreased expression of cartilage ECM genes and upregulation of inflammation associated genes. We found that Sirt5 mediated MaK is an important regulator of chondrocyte cellular metabolism and dysregulation of Sirt5-MaK could be an important mechanism underlying aging and obesity associated OA development.